Tumor Vascularity in Renal Masses: Correlation of Arterial Spin-Labeled and Dynamic Contrast Enhanced MR Imaging Assessments - Zhang, Yue (Clin Genitourin Cancer, 2015)
OBJECTIVE: To investigate potential correlations between perfusion by arterial spin-labeled (ASL) magnetic resonance imaging (MRI) and dynamic contrast enhanced (DCE) MRI derived quantitative measures of vascularity in renal masses >2 cm and to correlate these with microvessel density (MVD) in clear cell renal cell carcinoma (ccRCC). METHODS: Informed written consent was obtained from all patients before imaging in this HIPAA-compliant, IRB-approved, prospective study. 36 consecutive patients scheduled for surgery of a known renal mass >2 cm underwent 3T ASL and DCE MRI. ASL measures (P(ASL)) of mean, peak, and low perfusion areas within the mass were correlated to DCE-derived K(trans), Kep, and Ve in the same locations using a region of interest analysis. MRI data were correlated to MVD measures in the same tumor regions in ccRCC. Spearman correlation was used to evaluate the correlation between P(ASL) and DCE-derived measurements, and MVD. P<0.05 was considered statistically significant. RESULTS: Histopathologic diagnosis was obtained in 36 patients (25 men; mean age 58 ±12 years). P(ASL) correlated with K(trans) (ρ=0.48, P=0.0091 for the entire tumor and ρ=0.43, P=0.03 for the high flow area, respectively) and Kep (ρ=0.46, P=0.01 for the entire tumor and ρ=0.52, P=0.008 for the high flow area, respectively). P(ASL) (ρ=0.66, P=0.0002), K(trans) (ρ=0.61, P=0.001), and Kep (ρ=0.64, P=0.0006) also correlated with MVD in high and low perfusion areas in ccRCC. CONCLUSIONS: P(ASL) correlate with the DCE-derived measures of vascular permeability and flow, K(trans) and Kep, in renal masses >2cm in size. Both measures correlate to MVD in clear cell histology. MICROABSTRACT: Arterial spin labeling (ASL) and dynamic contrast-enhanced (DCE) magnetic resonance imaging (MRI) have been proposed to quantitatively assess vascularity in renal cell carcinoma (RCC). However there are intrinsic differences between these two imaging methods, such as the relative contribution of vascular permeability and blood flow to signal intensity for DCE MRI. We found a correlation between ASL perfusion (P(ASL)) and the DCE-derived K(trans), and Kep parameters in renal masses >2 cm in size and these measures correlated with microvessel density in clear cell RCC.